An Exploratory Study: Lack of Assertiveness and its Relation with Aggression and Appearance Anxiety - Hafsa Habib; Summiya Ahmad (Research Journal of Psychology, 2024)
Aggression and appearance anxiety are one of the crucial concerns in psychology, whereas human aggression and appearance anxiety has expected unlimited consideration. Even though some studies reported that self-assertiveness is associated to aggression and appearance anxiety, the mechanism whereby appearance anxiety and self-assertiveness affects aggression and appearance anxiety still unclear. This study explored the association between aggression and appearance anxiety cause self-assertiveness, as well as the outcome of self-appearance as a mediating factor. This research uses the Assertiveness scale, Appearance anxiety Scale, and the Buss-Perry Aggression Questionnaire. The association is explored by self-reported scales from N = 40 male and female from Peshawar university, Sarhad university, Iqra university and Hayatabad Medical Complex (HMC) in which n = 20 were male and n =20 were female, the average age was M = 21.3 years (SD = 3.147); Results showed that the aggression and appearance anxiety is related with lack of assertiveness. The higher the level of low assertiveness have positive relationship with the higher levels of aggression and appearance anxiety; Assertiveness was negatively related with aggression and appearance anxiety and positively correlated with low aggression and lack of appearance-anxiety. Keywords: self-assertiveness, aggression and appearance anxiety, mediating effect, appearance anxiety